A Perception on Post Implementation of Self Assessment Tax System on Selected Companies in East Coast Malaysia - Baba, Zaharah Salwati (2008)
This study examined taxpayer's perception and acceptability towards the self assessment tax system. The self assessment tax system applies to all companies and was implemented in 2001 . This empirical study covered three states - Terengganu, Kelantan and Pahang, involving 210 companies. Questionnaires were used to collect the data used in this study. Based on the findings of this research, it can be concluded that the implementation of self assessment system for taxpayers has not been successful because of a few limiting factors. One of the limiting factors towards successful implementation of the self assessment system is the lack of taxpayer's, knowledge of the tax system and the use of tax agent service is one of the causes why taxpayers have limited knowledge of the system. Results of the study revealed that most of the taxpayers welcome the change from the official assessment system to self assessment system. They know and understand their responsibility that they must compute their own tax under this system. Taxpayers also know that they must keep proper records of their business in order to enable the tax officer to conduct the audit. In addition, tax agents must fully understand this new system and they must fulfill their responsibilities in filling and returning the tax form to IRB. This study proposed a few recommendations to IRB to increase taxpayers' knowledge and understanding of the new system and IRB should take measures to overcome all the problems that arise to ensure the self assessment system is successfully implemented.